2018
DOI: 10.3329/ptcb.v28i2.39679
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Shootlets Multiplication and Callus Proliferation of Jojoba (Simmondsia chinensis) Plant

Abstract: A protocol for in vitro multiplication and callus proliferation of jojoba was developed. Nodal segments were cultured on MS supplemented with 1 mg/l BA. For multiplication, combination of 1.5 mg/l BA + 1 mg/l IAA resulted in greater number of shootlet. While, 1 mg/l BA + NAA enhanced the height of shootlet and number of nodes. Also, the effect of adenine sulfate and TDZ on shootlets multiplication was examined. The maximum number of shootlets emergence was obtained with medium contained 30 mg/l adenine sulfate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This agrees with the findings by Genady (2017) [50] where Picloram individually outperformed 2, 4-D to induce callus in Verbena bipinnatifida. Similar findings of Picloram being able to induce high frequency of callus was reported in Simmondsia chinensis (Bekheet et al, 2018) [51] and Cheilocostus speciosus (Hundare et al, 2017) [52] .…”
Section: Discussionsupporting
confidence: 80%
“…This agrees with the findings by Genady (2017) [50] where Picloram individually outperformed 2, 4-D to induce callus in Verbena bipinnatifida. Similar findings of Picloram being able to induce high frequency of callus was reported in Simmondsia chinensis (Bekheet et al, 2018) [51] and Cheilocostus speciosus (Hundare et al, 2017) [52] .…”
Section: Discussionsupporting
confidence: 80%
“…For instance, Kashanchi et al 15 reported callus induction of P. alkekengi in 1/2 MS medium supplied with 2, 4-D (2 mgL −1 ), and organogenesis was observed during callus growth. Picloram at 1 mgL −1 concentration increased markedly days to callus induction and callus diameter in gerbera 21 and also, in combination with BAP (5 mgL −1 ), induced maximum callus formation in Simmondsia chinensis 22 , which may be associated with its impact on cell elongation and division through the responsive gene expressions 23 . However, in Eupatorium adenophorum , picloram stimulated electrolyte leakage and malondialdehyde productions and decreased callus biomass at high concentrations 24 .…”
Section: Discussionmentioning
confidence: 93%
“…Applications of picloram, either individually or in combination with other PGRs, for callus induction were reported in different plant species, and similar results were found in support of the present experiment. For instance, maximum callus formation was found at 1 mg/l picloram in combination with 5 mg/l BAP in Simmondsia chinensis [ 19 ]. Likewise, 1 mg/l picloram outperformed NAA and 2,4-D resulting in maximum frequency (90%) of callus induction from pseudostem of Costus speciosus [ 15 ].…”
Section: Discussionmentioning
confidence: 99%